TERATOGENICITY TESTING OF SIDDHA FORMULATION OF NILAVEMBU KUDINEER ON ZEBRAFISH (DANIO RERIO) EMBRYO: TERATOGENICITY TESTING OF SIDDHA FORMULATION NILAVEMBU KUDINEER - SHANMUGAPRIYA P; ELANSEKARAN S; RAMAMURTHY M; JEEVA GLADYS R; SIVARAMAN D; CHRISTIAN GJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the study was to evaluate the teratogenic effect of Nilavembu Kudineer (NVK) by testing in zebrafish embryo (Danio rerio). Methods: The study consisted of 30 embryos/culture plate/dose concentration containing a series of diluted decoction of NVK ranging from 10 μg to 640 μg/ml, and the embryo development was monitored at specific time points. The parameters such as developmental abnormality and adverse events were monitored at 24 hourly intervals for 96 h. Results: The study results showed 100% hatching and survival of embryos with no significant abnormalities in the extension of study from 96 to 120 h post-fertilization examinations. Conclusion: NVK did not have teratogenic potential on testing it in various concentrations on zebrafish embryos validating its safety during pregnancy.